The Journey as Destination: Ibn ‘Arabi, Jacques Derrida, and Charles Taylor’s Creative Etymology in Contemporary ‘Social Imaginaries’ - Hussain, Ali (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This article investigates the importance of language as a carrier of meaning in the works of medieval Muslim polymath Ibn ‘Arabi (d. 1240) and contemporary philosophers Jacques Derrida (d. 2004) and Charles Taylor. Rather than focusing on the content of each figure’s writings on this topic, the research instead explores the writing style of Ibn ‘Arabi, specifically his use of etymology, as a creative endeavor to convey meaning in an indirect performance. After discussing Ibn ‘Arabi’s creative etymology, the paper concludes with a positioning of this conversation in contemporary discourses on language and society, particularly in Derrida’s seminal work Of Hospitality and two of Taylor’s monographs, The Language Animal and Social Imaginaries. Despite Taylor’s criticism of Derrida’s deconstructionist subjectivity, the former’s investment in ‘stories, images and legends’ paves the way for a more nuanced engagement with Derrida’s creative etymology and, by extension, Ibn ‘Arabi’s. The purpose of this excursion is twofold. First, to problematize Taylor’s critical view of postmodernism and Derrida’s school of deconstruction. Second, and more importantly, to highlight the relevance of Ibn ‘Arabi’s premodern prism of religion and mysticism for the contemporary – post-secular age.